Pendekatan Arsitektur Organik Pada Perancangan Panti Asuhan Berbasis Kewirausahaan Di Makassar - Baharuddin, Ihsan; Amin, Burhanuddin; Rahim, Rahmiani (TIMPALAJA : Architecture Student Journals, 2023)
_ Organic Architecture Approach on Entrepreneurship-based Orphanage Design in Makassar In society, the role of the orphanage is not merely to become the shelter for orphans but also to become the coffer of social life which is oriented towards their foster child’s growth. The relationship between een foster child and society is not merely such as the relationship between donor and beneficiary rather, it is a mutualistic relationship but by no means mutualistic in material terms. Society can be a donor in any social terms. The orphanage, which is one of the coffers of social life, can stimulate awareness of society related to the importance of the role and potential of children in the future through the management of orphanages based on entrepreneurship. The main purpose of implementing an entrepreneurial base is not solely to produce children who are experts at economic transactions but rather to instill the basic characteristics of entrepreneurs, such as honesty, responsibility, social spirit, and independence. Organic architecture applied as an architectural approach aims to meet the needs for space based on physical, social, and especially mental aspects by applying the “Youthful & Endless”. Organic architecture supports the entrepreneurial base by designing sustainable and attractive buildings by applying the “Living music” principle. The design also applies the “Of the hill” principle by designing a unified (single) building layout for the limited site area problem in Makassar.